Borges entre poesía y ontología (El Hilo de la Fabula, 2022)
The following article proposes an approach to the poetry of Jorge Luis Borges and analyzes, in a privileged way, the figure of the coin within his poetic work, particularly in the poems “A una Moneda”, “La Moneda de Hierro”, the sections “Quince monedas” and “Unas monedas” belonging  to the volume Obra poética (1923-1972) (1977). The purpose of this study is to highlight, on the one hand, the symbolic role of the coin within the author's lyrical economy and, on the other hand, its philosophical anchorage since the author chooses it as one of the privileged metaphors to represent his idea of ​​dichotomy and ambivalence as substance of reality.
Keywords: Jorge Luis Borges; poetry; coin; dichotomy; ambivalence